Infrared nano-spectroscopy of ferroelastic domain walls in hybrid improper ferroelectric Ca3Ti2O7 - K. A. Smith (Nature Portfolio, 2019)
Ferroic domain walls are nano-objects that are considered functional elements in future devices. Here, the authors study phonons across ferroelastic domain walls by synchrotron-based near-field infrared nano-spectroscopy and relate these changes to the order parameter which helps to understand domain wall dynamics.